Histopathological study of endometrium in cases of abnormal uterine bleeding - Bolde, Saroj A.; Pudale, Smita S.; Pandit, Gopal A.; Matkari, Pushkar P. (International Journal of Research in Medical Sciences, 2017)
Background:Abnormal uterine bleeding is one of the commonest complaints in women and when it occurs without organic lesions like tumor, inflammation, it is called as dysfunctional uterine bleeding. Aim of current study was to find out the histopathological pattern of endometrium in Abnormal Uterine Bleeding (AUB) also to study organic causes of AUB. Methods:Specimens received as endometrial curettage and hysterectomy specimens were studied followed by correlation of histopathology with age and clinical presentation. Results:The patients were mainly from the age group of 30-49 years (74.24%). The most common menstrual disorder was menorrhagia (46.86%). In dysfunctional uterine bleeding the most common histological pattern of endometrium includes proliferative endometrium (22.8%) followed by endometrial hyperplasia (19.40%), atrophic endometrium (7.16%), secretory endometrium (5.97%), irregular shedding [1.80%], irregular ripening (1.20%) and anovulatory endometrium (0.59%). Organic lesions encountered in AUB cases were leiomyoma (17.92%), endometrial polyp (1.79%), endometrial carcinoma (1.50%), endometriosis (0.59%) and choriocarcinoma (0.29%). Conclusion:It is important to know the histological pattern of the endometrium like proliferative endometrium, endometrial hyperplasia, atrophic endometrium, secretory endometrium, irregular ripening and shredding and organic lesions in patients diagnosed as AUB in different age groups since recognition of these conditions will help and will avoid further complications.